Polymer selection for nisoldipine solid dispersion to enhance solubility - Kyaw Oo, May; Chatterjee, Bappaditya (2015)
Nisoldipine is a very potent calcium channel blocker which is used as anti-hypertensive agent. Although it is prescribed widely as oral tablet, its use has been limited due to poor bioavailability which arises from its poor water solubility. Hot Melt solid dispersion of poorly water-soluble drug in long chain polymer is a common approach to enhance solubility and bioavailability. However, there is only little data available on the selection of polymer type and ratio which are critical parameters for solid dispersion. The present study aimed to compare the effect of different polymers on nisoldipine solid dispersion and to investigate the type and range of polymers with optimum nisoldipine solubility.